The Feasibility of Carbon Capturing, Storage and Utilization Projects in Developing Countries: A Case of Malaysia - Ibrahim, Mohammed Yussoff; Ghazali, Zulkipli; Rahman, Haseeb Ur (International Journal of Economics and Financial Issues, 2016)
The rapid change in climate and the high cost of controlling it are the issues caught much attention around the world especially during the last two decades. The CCSU (Carbon Capture, Storage and Utilization) is widely believed the mechanism to control both these issues to a great extent. However, the adoption, expansion, or development of CCSU isn’t yet common to counter these issues. The pace of CCSU adoption and development is greatly impaired by its high cost and non-availability of funds in both developed and developing countries of the world. The scenario in developing countries is worse as these countries have no mandatory obligation for carbon emissions like developed countries. Subsequently, most of the developing countries except few are not willing to carry out CCSU operations voluntarily. This paper, therefore, sheds light on various costs associated to CCSU operations and the potential sources of financing them in developing countries especially Malaysia. The paper concludes that public awareness is fundamental in persuading governments and other entities to finance CCSU operations and ensuring the feasibility, economic viability and success of these projects. The paper recommends that governments, environmental agencies, international financial institutions, and developed countries should support CCSU projects in developing countries by providing funds and capacity building measures. The paper contributes to the limited literature and policy making of CCSU funding especially in developing countries like Malaysia where the mechanism (CCSU) is yet in embryonic stage. Keywords - CCSU, Public Awareness, Developing countries, Malaysia JEL Classifications: L13, Q32